The Mechanical Research of Vertical Screw Conveyor Particle Group Based on the Radial Change of Material Speed. Issue 3 (June 2021) - Mei, Lei; Cheng, Chuang; Fan, Ziqiang
Abstract: This paper establishes a granular mechanics model for the stable movement of the material particle group in the vertical screw unloader with the granular mechanics, continuum mechanics and particle group theory and innovatively proposed the hypothesis that the speed of the material particle group changes radially in the spiral groove. Through the analysis of the material movement, the movement characteristic parameters of the material are determined. The study found that the material free surface type of the longitudinal section of the conveyor and its identification and solution methods and the pressure distribution law of the material particle group on the conveying pipe wall and spiral surface. In this paper, the granular mechanics, continuum mechanics and particle group theory are used to establish a granular mechanics model for the stable movement of the material particle group in the vertical screw unloader. We innovatively proposed the hypothesis that the speed of the material particle group changes radially in the spiral groove and determined the material movement characteristic parameters through the analysis of the material movement.